Calitatea vieții – element fundamental în proiectarea noii societăți - Mățăuan, Gabriel; Vrânceanu, Radu (Calitatea Vieții, 1990)
Socialism and capitalism are not obsolete notions. They still co-exist as sociai systems. Although they are fundamentally different, they have one element in common: the lack of a coherent policy for improving the QL. Socialism has failed. Capitalism is operative but has shown imperfections which impair the quality of life. A proposal is made in order to design a society whose strategic goal be the maximization of QL. In order to reach this goal and in agreement with the definition of QL as an evaluating concept, the authors suggest several lines of action which have in view the actual life conditions, the individual requirements an the evalution process.